The Effectiveness of Understanding The Concept of Worship and Islamic Religious Education by Organizing A Islamic Boarding School Activities for Elementary School Students - Syahriani, Syahriani (Jurnal Basicedu, 2021)
This study aims to describe the effectiveness of understanding the concept of worship and Islamic religious education by organizing lightning boarding activities for fourth grade students of SDN 101821 Pancurbatu in the second semester of T.P. 2018/2019. This research uses action research with three cycles (rounds). Each cycle (round), consists of four stages, namely design, activity and observation, reflection and revision. The data obtained in the form of formative test results, observation sheets of teaching and learning activities. From the results of the analysis, it was found that the conclusions that can be drawn from this CAR are (1) student activity tends to increase by learning using a simulation of flash boarding school activities; (2) Students' cooperative skills during the learning process using the simulation of flash boarding activities can appear and most of them show an increase in Islamic learning achievement; (3) Islamic learning achievement in students has increased significantly after being implemented through learning using a simulation of Islamic boarding school activities. It is recommended that learning in the field of Islamic studies is time to be replaced with innovative learning techniques such as using a simulation of Islamic boarding school activities for elementary students.